2010
DOI: 10.1002/jbm.a.32797
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biological evaluation of electrospun cellulose acetate fiber mats containing asiaticoside or curcumin

Abstract: Ultra-fine cellulose acetate (CA; M(w) approximately 30,000 Da; degree of acetyl substitution approximately 2.4) fiber mats containing either asiaticoside [from the plant Centella asiatica (L.); either in the form of a crude extract (CACE) or pure substance (PAC)] or curcumin (CM; from the plant Curcuma longa L.) were successfully prepared. The proposed use of these materials is as topical/transdermal patches or wound dressings. Here, the potential for use of these herb-loaded CA fiber mats as wound dressings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…To disinfect the bacteria attack, numerous active ingredients such as silver [16,17] and iodine complex [18] have been studied. The immobilization of silver to polyvinyl alcohol nanofiber mats showed good antibacterial activity and enhanced a moist environment [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To disinfect the bacteria attack, numerous active ingredients such as silver [16,17] and iodine complex [18] have been studied. The immobilization of silver to polyvinyl alcohol nanofiber mats showed good antibacterial activity and enhanced a moist environment [16].…”
Section: Introductionmentioning
confidence: 99%
“…The immobilization of silver to polyvinyl alcohol nanofiber mats showed good antibacterial activity and enhanced a moist environment [16]. Iodine has been incorporated into polyvinylpyrrolidone solution to prepare iodine containing polyvinylpyrrolidone nanofiber mats and the slow release of iodine from the electrospun nanofibers has been studied [19].…”
Section: Introductionmentioning
confidence: 99%
“…18,19 The up-regulation of collagen and the increase of tensile strength of guinea pig wounds with topical treatment of varying dosage were observed. 20 Moreover, Suwantong et al 21 observed an increase in synthesized collagen by fibroblasts which had been cultured on a cellulose acetate (CA) fiber mat containing pure AC at a high loading amount (i.e., 40% (wt/wt), based on the weight of CA) in comparison with those cultured on a neat CA fiber.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the cyclohexene ring moiety of AC is captivated well within the HPβCD cavity (Figure 1(b)). 27 According to Suwantong et al, 21 the efficacy of AC loaded within the electrospun CA fibers in promoting the production of collagen of cultured fibroblasts was only observed at a high concentration of 40% (wt/wt). Here, we aimed to use HPβCD to improve the efficacy of AC at a much lower concentration of AC (i.e., at 10% (wt/wt)).…”
Section: Introductionmentioning
confidence: 99%
“…Silk nanofiber mats were electrospun with epidermal growth factor to promote wound healing process (Schneider et al, 2009a), and it has been found the functionalized mat increased the wound closure by 90%. An anti-cancer, anti-oxidant and anti-flammatory substance, curcumin, was loaded into PCL (Merrell et al, 2009) and CA (Suwantong et al, 2010) nanofibers for wound dressing. These dressings were superior in supporting human dermal fibroblast attachment and proliferation and exhibited high rate of wound closure.…”
Section: Wound Healingmentioning
confidence: 99%